JURIDICAL ANALYSIS OF CHILD VICTIMS OF CYBERBULLYING THROUGH SOCIAL MEDIA REVIEWED FROM THE PERSPECTIVE OF CRIMINAL RESPONSIBILITY - Fitria Ramadhani Siregar; Zufarnesia (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
Children as part of the young generation are one of the potential human resources and as a successor to the ideals of the nation's struggle in the future. potential human resources and as a successor to the ideals of the nation's struggle in the present and future. current and future. Children have a strategic role and have special characteristics and characteristics, so they need guidance and protection in order to ensure the growth and development of physical, mental in order to ensure balanced physical, mental, and social growth and development. in a balanced manner. According to Indonesian law, the State has provided protection to children through various laws and regulations. The child is one of the legal subjects in this country is also subject to and obedient to the applicable rules of law, especially in terms of legal arrangements regarding cyberbullying. applicable laws, especially in terms of legal arrangements regarding cyberbullying, which occurs with cyberbullying, which occurs a lot with the means of social media on the internet, where many children become. The formulation of the problem that will be the subject of discussion is; How is the juvenile criminal justice system in Indonesia in a normative legal review? How is the criminal aspect of cyberbullying behavior against children committed by means of social media on the internet? conducted by means of social media on the internet? criminal responsibility of children as victims of cyberbullying committed by means of social media on the internet? social media on the internet? The crime of corruption is one part of special criminal law in addition to having certain specifications that are different from general criminal law, such as the existence of procedural law deviations and when viewed from the material regulated, the crime of corruption is directly or indirectly intended to minimize leakage and irregularities in the state's finances and economy.This research uses descriptive research, with a qualitative research type, and uses normative juridical research. qualitative research, and uses normative juridical research type, and this research uses library research method.